Substituent Effects on the Low-Frequency Vibrational Modes of Benzoic Acid and Related Compounds - 葛敏 赵红卫 王文锋 余笑寒 李文新 (Chinese journal of chemistry, 2007)
Well-resolved absorption spectra of benzoic acid and its derivatives with one hydrogen atom replaced by a substituent group CH3, OH, NH2 or NO2 were reported in the frequency region between 6 and 67 cm^-1 at room temperature with terahertz time-domain spectroscopy （THz-TDS）. These substances can be distinguished easily based on the terahertz absorption spectra. The measurements suggested that even minor changes in the molecular configuration and chemical composition lead to distinct differences in THz spectrum. Density functional theory （DFT） method was used to assist the analysis and assignment of the individual THz absorption spectra of benzoic acid and its methyl derivatives. Observed THz responses of samples can be assigned to the collective vibrations associated with intermolecular hydrogen bonds.